2014
DOI: 10.1016/j.devcel.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The Dpp/TGFβ-Dependent Corepressor Schnurri Protects Epithelial Cells from JNK-Induced Apoptosis in Drosophila Embryos

Abstract: SummaryJun N-terminal kinase (JNK) often mediates apoptosis in response to cellular stress. However, during normal development, JNK signaling controls a variety of live cell behaviors, such as during dorsal closure in Drosophila embryos. During this process, the latent proapoptotic activity of JNK becomes apparent following Dpp signaling suppression, which leads to JNK-dependent transcriptional activation of the proapoptotic gene reaper. Dpp signaling also protects cells from JNK-dependent apoptosis caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The role of JNK signalling during dorsal closure has also been shown to rely on additional signalling pathways. Transforming growth factor-β (TGF-β) signalling, activated by Dpp, has been demonstrated as acting to suppress the pro-apoptotic activity of the JNK signalling pathway -while the JNK-induced AP-1 TF complex promotes rpr expression and apoptosis, the TGF-β-induced TF Schnurri (Shn) suppresses rpr expression (Beira et al, 2014). This is an elegant example of how JNK signals can be co-opted during developmental events, like in tumourigenesis, via the mechanism of apoptosis suppression.…”
Section: Regulating Jnk Signalling In Development and Tissue Homeostasismentioning
confidence: 99%
“…The role of JNK signalling during dorsal closure has also been shown to rely on additional signalling pathways. Transforming growth factor-β (TGF-β) signalling, activated by Dpp, has been demonstrated as acting to suppress the pro-apoptotic activity of the JNK signalling pathway -while the JNK-induced AP-1 TF complex promotes rpr expression and apoptosis, the TGF-β-induced TF Schnurri (Shn) suppresses rpr expression (Beira et al, 2014). This is an elegant example of how JNK signals can be co-opted during developmental events, like in tumourigenesis, via the mechanism of apoptosis suppression.…”
Section: Regulating Jnk Signalling In Development and Tissue Homeostasismentioning
confidence: 99%
“…It has now been found that JNK-mediated apoptosis signal is integrated at the reaper regulatory sequences, together with other anti-apoptotic signals. DPP signaling, mediated by the transcription factor Schnurri, represses JNK-mediated reaper expression through a binding site located in between those of AP-1 (Beira, 2014) (Figure 2). During embryonic development, dorsal closure is regulated by JNK signaling, but these cells do not undergo apoptosis, due to Dpp-Schnurri mediated repression of IAP-antagonist gene expression.…”
Section: Transcriptional Regulation Of Drosophila Iap-antagonistsmentioning
confidence: 99%
“…In addition, we took into account SE variants which deviate from these two motifs, yet have been demonstrated to be functional in biochemical and/or in vivo reporter assays. The motifs included the SE -variant GRCKNC(N) 5 GTCTG derived from the analysis of the BMP-dependent Xvent2 promoter (Yao et al, 2006), and low affinity binding sites recently identified in brk , msh (also known as Drop) and reaper ( rpr ) (Beira et al, 2014; Esteves et al, 2014; Gafner et al, 2013). The later motifs deviate from the SE at nucleotide positions 1 or 3 of the original SE motif.…”
Section: Methodsmentioning
confidence: 99%